2017 International Conference on Electrical Engineering and Informatics (ICELTICs) 2017
DOI: 10.1109/iceltics.2017.8253238
|View full text |Cite
|
Sign up to set email alerts
|

Forecast on vietnam electricity consumption to 2030

Abstract: Abstract-The first but very significant step in electricity system planning is to make an accurate long-term forecast on electricity consumption. This article aims to forecast the consumption for

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…This method has been widely applied in researches of developing countries, such as Malaysia 4 , Pakistan 5 , and China 6 , etc. The strengths of Cobb Douglas production function are that: (1) it provides detail information about the stable and the changeability of variables and forecasted values; (2) it could be used to investigate the influential factors or variables impacting on forecasted results; and (3) it is a practical method which is easy to be analyzed and calculated 7 . Despite all these advantages, there is no record about experience on applying this method in forecasting long-term electricity demand for the industry and construction sectors.…”
Section: Introductionmentioning
confidence: 99%
“…This method has been widely applied in researches of developing countries, such as Malaysia 4 , Pakistan 5 , and China 6 , etc. The strengths of Cobb Douglas production function are that: (1) it provides detail information about the stable and the changeability of variables and forecasted values; (2) it could be used to investigate the influential factors or variables impacting on forecasted results; and (3) it is a practical method which is easy to be analyzed and calculated 7 . Despite all these advantages, there is no record about experience on applying this method in forecasting long-term electricity demand for the industry and construction sectors.…”
Section: Introductionmentioning
confidence: 99%
“…Electricity consumption is growing nowadays especially in developing countries like Vietnam along with economy transformation [1]. According to the recent forecasting consumption, Vietnam electricity system will need more than 500GWh by the year 2030 [2][3][4][5]. The latest master plan for the power system of the country revealed that a half of that figure will be supplied by coal-fired thermal power plants [6].…”
Section: Introductionmentioning
confidence: 99%